Experience Matters: Early Literacy Beliefs and Pedagogical Orientations Among Indonesian Early Childhood Education Teachers - Machmud, Hadi; Abidin, Azwar; Alim, Nur; Marlina, Marlina; Anhusadar, Laode (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
This study examines how professional status and teaching experience shape early literacy beliefs and pedagogical orientations among Indonesian early childhood education (ECE) teachers and pre-service teachers. Using a convergent mixed-methods design, the study collected questionnaire and open-ended response data from 253 participants, including 136 in-service classroom teachers and 117 pre-service teachers, across 41 ECE institutions in Central Indonesia. Exploratory factor analysis of the literacy belief items identified three dimensions: Literacy Practice and Environment (α = 0.89; ω = 0.91), Assessment and Correction (α = 0.78; ω = 0.81), and Formal Instruction and Parental Involvement (α = 0.81; ω = 0.83). Analysis of pedagogical orientation items produced two dimensions: Teacher-Centered (ω = 0.84) and Student-Centered (ω = 0.82). Participants showed stronger endorsement of student-centered orientations (M = 4.229, SD = 0.386) than teacher-centered orientations (M = 3.403, SD = 0.522). Group comparisons indicated significant differences in literacy beliefs according to professional status and teaching experience, especially in Literacy Practice and Environment and Assessment and Correction. Qualitative responses helped explain these patterns by showing that teachers negotiate developmental principles, structured guidance, parental expectations, and school-readiness demands in daily literacy practice. The findings suggest that Indonesian ECE teachers do not simply shift from formal instruction to child-centered pedagogy. Rather, they construct hybrid literacy practices that combine environmental support, explicit guidance, and relational responsiveness. This study contributes evidence from an underrepresented Indonesian ECE context and highlights the need for teacher education and professional development that support adaptive, context-sensitive early literacy pedagogy across career stages.